Qualitative C-reactive protein as a marker of neonatal sepsis in a tertiary neonatal unit in Sudan - Abdelmoneim E. Kheir; Ghada A. Jobara; Kamal M. Elhag; Mohamed Z. Karar (PAGEPress Publications, 2013)
Sepsis is one of the most common causes of morbidity and mortality in newborns. Diagnosis of neonatal sepsis may be difficult because clinical presentations are often non-specific. The aim of this study was to evaluate the role of qualitative C-reactive protein in the diagnosis of neonatal sepsis, and examine the correlation between C-reactive protein, blood culture and risk factors for sepsis. This was a prospective study, conducted in the Neonatal Intensive Care Unit at Soba University Hospital, Sudan. A total of seventy babies with a clinical diagnosis of sepsis were included. Chi square test was used to determine the association between C-reactive protein and risk factors for sepsis and also the association between C-reactive protein and blood culture. Blood culture was positive in 41.4% of babies, and C-reactive protein was positive in 58% of babies with positive blood culture. There was significant association between C-reactive protein results and blood culture (P=0.00). In conclusion, we can assume that Creactive protein is a reliable diagnostic marker of neonatal sepsis, especially in developing communities with poor resources.